Classification Of Brainwave Using Data Mining In Producing An Emotional Model - Khairul Anuar; Nurshuhada Mahfuz; Md Jan Nordin; Waidah Ismail; Mohd Zalisham Jali (Little Lion Scientific, 2024)
Journal of Theoretical and Applied Information Technology 20th May 2015 -- Vol. 75. No. 2 -- 2015